2010
DOI: 10.7150/ijbs.6.199
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling oxidative/energy metabolism with low sub chronic doses of 3-nitropropionic acid or iodoacetate in vivo produces striatal cell damage

Abstract: A variety of evidence suggests that the failure of cellular metabolism is one of the underlying causes of neurodegenerative diseases. For example, the inhibition of mitochondrial function produces a pattern of cellular pathology in the striatum that resembles that seen in Huntington's disease. However, neurons can also generate ATP through the glycolytic pathway. Recent work has suggested a direct interaction between mutated huntingtin and a key enzyme in the glycolytic pathway, glyceraldehyde-3-phosphate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Naringin restores the level of GSH in 3-NPinduced rats and decreased the levels of ROS possibly by directly scavenging the ROS or through the transcriptional up-regulation of antioxidant genes (Jeon et al, 2001). Excessive generation of ROS by 3-NP directs mitochondrial dysfunction in ultrastructural levels with swollen and disorganised cristae and is consistent with many earlier studies (Rodrı´guez et al, 2010). However, in the naringin-treated group of animals, we observed a significant amelioration in above abnormal ultrastructures and establishing its protective efficacy against 3-NPinduced neurodegeneration.…”
Section: Discussionsupporting
confidence: 88%
“…Naringin restores the level of GSH in 3-NPinduced rats and decreased the levels of ROS possibly by directly scavenging the ROS or through the transcriptional up-regulation of antioxidant genes (Jeon et al, 2001). Excessive generation of ROS by 3-NP directs mitochondrial dysfunction in ultrastructural levels with swollen and disorganised cristae and is consistent with many earlier studies (Rodrı´guez et al, 2010). However, in the naringin-treated group of animals, we observed a significant amelioration in above abnormal ultrastructures and establishing its protective efficacy against 3-NPinduced neurodegeneration.…”
Section: Discussionsupporting
confidence: 88%
“…We previously demonstrated that GAPDH levels vary with the experimental protocol [15] , therefore we evaluated β-actin and ribosomal 18S in the present study.…”
Section: Selection Of Reference Genesmentioning
confidence: 99%
“…The assay was performed at 48 h after the last dose following the methodology in our previous report [15] using an apoptosis detection kit …”
Section: Terminal Deoxynucleotidyl Transferase Dutpmentioning
confidence: 99%
See 2 more Smart Citations